2005
DOI: 10.1021/ef0497107
|View full text |Cite
|
Sign up to set email alerts
|

Solids Deposition from Multicomponent Wax−Solvent Mixtures in a Benchscale Flow-Loop Apparatus with Heat Transfer

Abstract: The deposition of solids from mixtures of a paraffinic wax (C20−C40) dissolved in a multicomponent solvent (C9−C16) was studied under laminar flow conditions. A novel benchscale flow loop was developed, which consisted of a jacketed heat-exchange section for solids deposition on the inner surface of an aluminum tube. Experiments were performed to investigate the effects of the wax−solvent mixture composition, hot and cold stream temperatures, flow or shear rate, deposition residence time, and hydrodynamic entr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

53
215
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 49 publications
(270 citation statements)
references
References 31 publications
53
215
2
Order By: Relevance
“…In the heat‐transfer approach, the liquid‐deposit interface temperature is taken to be equal to the WAT of the wax solution throughout the deposition process. Batch cooling studies under static and sheared conditions and bench‐scale flow‐loop studies have confirmed the interface temperature ( T d ) to remain constant, and close to the WAT, during the gelling and deposit‐growth periods. It is also pointed out that the heat‐transfer approach has been validated with experimental measurements under both the ‘hot flow’ (i.e.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…In the heat‐transfer approach, the liquid‐deposit interface temperature is taken to be equal to the WAT of the wax solution throughout the deposition process. Batch cooling studies under static and sheared conditions and bench‐scale flow‐loop studies have confirmed the interface temperature ( T d ) to remain constant, and close to the WAT, during the gelling and deposit‐growth periods. It is also pointed out that the heat‐transfer approach has been validated with experimental measurements under both the ‘hot flow’ (i.e.…”
Section: Introductionmentioning
confidence: 82%
“…One important observation about the deposition process, at steady state, is that the liquid‐deposit interface temperature, T d , has been shown to be constant and equal to the WAT . That is, the temperature, T d , between R h and R d is constant (and equal to the WAT of the ‘waxy’ mixture).…”
Section: Heat‐transfer Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…While flow loop deposition studies date back several decades (Jessen and Howell, 1958;Cole and Jessen, 1960;Hunt, 1962;Jessen and Mendell, 1970;Mendell and Jessen, 1972;Weingarten and Euchner, 1988) more recent work has focused on the fundamental understanding to the deposition process, as well as the ability to accurately model deposition behavior (Burger et al, 1981;Brown et al, 1993;Creek et al, 1999;Singh et al, 2000;Apte et al, 2001;Singh et al, 2001a,b;Matzain et al, 2002;Paso and Fogler, 2003;Venkatesan and Fogler, 2004;Parthasarathi and Mehrotra, 2005;Merino-Garcia et al, 2007). A survey of such studies shows that four key factors determine the rate and nature of the deposit formed: the flow rate (Weingarten and Euchner, 1988;Creek et al, 1999;Singh et al, 2000), the temperature field, (Cole and Jessen, 1960;Burger et al, 1981;Creek et al, 1999;Singh et al, 2000) the composition of the oil Singh et al, 2001b), and the nature of the surface (Cole and Jessen, 1960;Parks, 1960;Jorda, 1966;Kok and Saracoglu, 2000;Zhang et al, 2002).…”
Section: Background On Wax Depositionmentioning
confidence: 99%